Anode active material for lithium secondary battery and methode of manufacturing the same

KR1020260131089APending Publication Date: 2026-09-01SK ON CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020260147927
Authority / Receiving Office
KR · KR
Patent Type
Applications
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-09-01

Smart Images

  • Figure PAT00001_ABST
    Figure PAT00001_ABST
Patent Text Reader

Abstract

According to embodiments of the present invention, a negative electrode active material for a lithium secondary battery is provided, comprising carbon-based particles and a coating layer bonded to at least a portion of the surface of the carbon-based particles, wherein the coating layer comprises boron and a conductive material. Due to the coating layer, the electrolyte decomposition reaction is suppressed, and the capacity and cycle life of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a negative electrode active material for a lithium secondary battery and a method for manufacturing the same. Background Technology

[0002] Rechargeable batteries are batteries capable of repeated charging and discharging, and with the advancement of the information and communication and display industries, they are widely applied as power sources for portable electronic communication devices such as camcorders, mobile phones, and laptop PCs. Furthermore, recently, battery packs containing rechargeable batteries are being developed and applied as power sources for eco-friendly vehicles, such as hybrid cars.

[0003] Examples of secondary batteries include lithium-ion batteries, nickel-cadmium batteries, and nickel-hydrogen batteries; among these, active research and development is being conducted on lithium-ion batteries due to their high operating voltage and energy density per unit weight, as well as their advantages in charging speed and weight reduction.

[0004] A lithium secondary battery may include an electrode assembly comprising a positive electrode, a negative electrode, and a separator, and an electrolyte impregnating the electrode assembly. The lithium secondary battery may further include an outer casing, for example, in the form of a pouch, that accommodates the electrode assembly and the electrolyte.

[0005] For example, a lithium secondary battery may include a negative electrode such as a carbon material capable of absorbing and releasing lithium ions, a positive electrode made of a lithium-containing oxide, and a non-aqueous electrolyte in which an appropriate amount of lithium salt is dissolved in a mixed organic solvent.

[0006] When carbon-based materials are applied as negative electrode active materials in lithium-ion batteries, the charge-discharge potential of lithium is lower than the stable range of conventional non-aqueous electrolytes, leading to electrolyte decomposition reactions during charging and discharging. Consequently, a Solid Electrolyte Interface (SEI) film forms on the surface of the carbon-based negative electrode active material. This film undergoes repeated decomposition and formation through repeated charge-discharge cycles. The formation of this unstable film degrades the initial charge-discharge efficiency, high-rate performance, and lifespan characteristics of the lithium-ion battery.

[0007] For example, Korean Registered Patent Publication No. 10-0326446 discloses a negative electrode active material to which a spherical carbon-based material is applied, but deterioration of charge / discharge efficiency and lifespan characteristics may occur due to electrolyte decomposition reactions. Prior art literature

[0008] Korean Registered Patent Publication No. 10-0326446 The problem to be solved

[0009] One objective of the present invention is to provide a negative electrode active material for a lithium secondary battery with improved operational stability and electrical characteristics, and a method for manufacturing the same.

[0010] One objective of the present invention is to provide a lithium secondary battery with improved operational stability and electrical characteristics.

[0011] One objective of the present invention is to provide a negative electrode active material in which gas generation is reduced or substantially absent during the formation process, and a lithium secondary battery comprising the same. means of solving the problem

[0012] A negative electrode active material for a lithium secondary battery according to exemplary embodiments of the present invention comprises carbon-based particles and a coating layer bonded to at least a portion of the surface of the carbon-based particles, wherein the coating layer may comprise boron (B) and a conductive material.

[0013] In some embodiments, the coating layer may include boron oxide.

[0014] In some embodiments, the conductive material may include a linear conductive material.

[0015] In some embodiments, the linear conductive material may include at least one of carbon nanotubes (CNT), carbon nanofibers (CNF), metal fibers, vapor-grown carbon fibers (VGCF), and graphene.

[0016] In some embodiments, the metal fiber may comprise at least one metal or an alloy thereof selected from copper (Cu), nickel (Ni), aluminum (Al), iron (Fe), silver (Ag), gold (Au), platinum (Pt), zinc (Zn), and titanium (Ti).

[0017] In some embodiments, the carbon-based particles may include at least one of artificial graphite, natural graphite, graphitized carbon fiber, graphitized mesocarbon microbeads, petroleum coke, resin calcined body, carbon fiber, activated carbon, and pyrolytic carbon.

[0018] In some embodiments, the content ratio of the conductive material to the boron may be 0.1 to 30% by weight.

[0019] In some embodiments, the thickness of the coating layer may be 10 to 100 nm.

[0020] A method for manufacturing a negative electrode active material for a lithium secondary battery according to exemplary embodiments of the present invention may include the steps of: preparing carbon-based particles; preparing a coating solution by dispersing a boron (B) source and a conductive material in a solvent; mixing the carbon-based particles and the coating solution to produce a mixture; and heat-treating the mixture.

[0021] In some embodiments, the mixing weight ratio of the boron source and the conductive material may be 20:1 to 2:1.

[0022] In some embodiments, the solvent may include at least one of water or ethanol.

[0023] In some embodiments, the heat treatment is performed in an atmospheric or inert gas atmosphere and can be performed at 400 to 600°C.

[0024] A lithium secondary battery according to exemplary embodiments of the present invention may include a negative electrode comprising a negative electrode active material for a lithium secondary battery; a positive electrode; and a separator interposed between the negative electrode and the positive electrode. Effects of the invention

[0025] A negative electrode active material for a lithium secondary battery according to exemplary embodiments of the present invention comprises carbon-based particles and a coating layer bonded to at least a portion of the surface of the carbon-based particles, wherein the coating layer may include boron and a conductive material. Accordingly, the inorganic coating layer can suppress the electrolyte decomposition reaction and improve the capacity and cycle life of the battery.

[0026] According to some exemplary embodiments, the conductive material may include a linear conductive material. Accordingly, the mechanical strength of the coating layer can be improved to prevent delamination of the coating layer, and an electron transfer path between particles can be formed to improve the output performance of the battery.

[0027] A lithium secondary battery according to exemplary embodiments of the present invention may include a negative electrode active material comprising carbon-based particles and a coating layer bonded to at least a portion of the surface of the carbon-based particles and comprising boron (B) and a conductive material. Accordingly, productivity can be improved by simplifying or omitting the formation process by reducing or removing the formation gas generated during the initial formation process. Brief explanation of the drawing

[0028] FIGS. 1 and FIGS. 2 are a schematic plan view and a cross-sectional view, respectively, showing a lithium secondary battery according to exemplary embodiments. Figure 3 is a scanning electron microscope image of the surface of artificial graphite magnified. Figure 4 is a scanning electron microscope image showing the surface of artificial graphite after calcination treatment at 500°C in an air atmosphere. Figure 5 is a scanning electron microscope image showing the surface of the cathode active material particles of Example 1 after calcination treatment at 500°C in an air atmosphere. Specific details for implementing the invention

[0029] According to embodiments of the present invention, a negative electrode active material for a lithium secondary battery is provided, comprising carbon-based particles and a coating layer bonded to at least a portion of the surface of the carbon-based particles, wherein the coating layer comprises boron and a conductive material. Additionally, embodiments of the present invention provide a lithium secondary battery comprising a negative electrode manufactured from the negative electrode active material.

[0030] Embodiments of the present invention will be described in more detail below with reference to the drawings. However, the following drawings attached to this specification are intended to illustrate preferred embodiments of the present invention and serve to further enhance understanding of the technical concept of the present invention together with the aforementioned description; therefore, the present invention should not be interpreted as being limited only to the matters described in such drawings.

[0031] < Negative active material for lithium secondary batteries and method for manufacturing the same >

[0032] The cathode active material according to embodiments of the present invention may include carbon-based particles and a coating layer bonded to at least a portion of the surface of the carbon-based particles and comprising boron (B) and a conductive material.

[0033] The negative electrode active material for a lithium secondary battery functions to absorb and extract lithium ions, and carbon-based particles can be used as the material. The carbon-based particles may include, for example, at least one of artificial graphite, natural graphite, graphitized carbon fiber, graphitized mesocarbon microbeads, petroleum coke, resin calcined body, carbon fiber, activated carbon, and pyrolytic carbon.

[0034] Average particle size (D) of the above carbon-based particles 50 ) may be, for example, about 7 μm to about 30 μm, but is not limited thereto. For example, the carbon-based particles may include secondary particles having an average particle size of 10 to 25 μm formed by including primary particles having an average particle size of 5 to 15 μm.

[0035] The above coating layer is a coated layer bonded to at least a portion of the surface of the carbon-based particles, and the negative electrode active material according to the embodiments of the present invention can improve the capacity and cycle life of the battery and improve the output performance of the battery by having a coating layer.

[0036] In exemplary embodiments, the coating layer may include boron and a conductive material. The coating layer may include boron to suppress the electrolyte decomposition reaction and improve the irreversible capacity of the battery. Additionally, since electrons can easily move through the conductive material while including an inorganic coating layer, the output performance and lifespan of the battery may be improved.

[0037] In addition, the cathode active material according to the embodiments of the present invention can secure oxidation resistance against sintering treatment because the coating layer containing boron and a conductive material is formed on the surface of carbon-based particles.

[0038] Figures 3 and 4 are scanning electron microscope images of the surface of artificial graphite particles and the surface of said artificial graphite particles after being calcined in an air atmosphere at 500°C, respectively, and Figure 5 is a scanning electron microscope image of the surface of said artificial graphite particles after forming a coating layer containing boron and a conductive material on the surface of said artificial graphite particles and then calcining it in an air atmosphere at 500°C.

[0039] According to Fig. 3, the surface of the carbon-based particles before calcination is uniform, and the specific surface area of ​​the artificial graphite used for observation is 2.19 m² 2 It was measured as / g. Figure 4 shows the surface area observed after high-temperature calcination of the artificial graphite, and the specific surface area is 2.39 m². 2 It is measured as / g. Fig. 5 shows the surface observed after forming the coating layer of the present invention on the artificial graphite particles of Fig. 3 and then subjecting them to high-temperature calcination treatment in the same manner as the artificial graphite particles of Fig. 4. The specific surface area of ​​the graphite particles with the coating layer formed in Fig. 5 is 2.17 m². 2 It is measured in / g. Referring to Fig. 5, it can be seen that when B2O3 is coated in excess at 3%, a thick coating layer is formed and has an uneven surface shape.

[0040] Accordingly, the negative electrode active material of the present invention can secure resistance to oxidation reactions caused by high-temperature calcination treatment by forming the coating layer. Accordingly, a lithium secondary battery comprising the negative electrode active material of the present invention with the coating layer formed thereon can reduce or eliminate the formation gas generated during the initial formation process, and the productivity of the lithium secondary battery can be improved.

[0041] In some exemplary embodiments, the boron may be present in the coating layer in the form of the element alone or as a compound with other elements. The boron compound may include, for example, boron oxide. For example, B2O3, H3BO3, etc. may be included in the coating layer. Accordingly, the coating layer may be formed by mixing a coating solution containing boron oxide (B2O3), boric acid (H3BO3), etc. with the carbon-based particles.

[0042] In exemplary embodiments, the conductive material may include a particulate conductive material and / or a linear conductive material, and preferably may include a linear conductive material.

[0043] In the present invention, "linear conductive material" refers to a conductive material having a large aspect ratio, for example, a fibrous structure. The linear conductive material is electrochemically stable and possesses good conductivity, and it is preferable to form a fibrous structure. The shape of the fibrous structure is not particularly limited and may be, for example, cylindrical or hollow. The linear conductive material can effectively form an electrically conductive network of the coating layer and can achieve excellent ion conductivity for lithium ions.

[0044] The aspect ratio of the linear conductive material may be 2 or more, 3 or more, 4 or more, 5 or more, 10 or more, 20 or more, 50 or more, or 100 or more. In this case, the aspect ratio of the linear conductive material may be defined as the ratio of the maximum value to the minimum value of the length of any two ends of the conductive material. Accordingly, the linear conductive material can be dispersed three-dimensionally within the coating layer to form a conductive network and improve the electrical conductivity of the cathode.

[0045] For example, the linear conductive material may be one or more selected from the group consisting of fine fiber carbon having a diameter of less than 100 nm and fibrous carbon having a diameter of 100 nm or more. Accordingly, the electrical conductivity of the negative electrode active material is improved and the mechanical strength of the coating layer is improved, thereby preventing the detachment of the coating layer even during repeated charging and discharging.

[0046] In some exemplary embodiments, the linear conductive material may comprise at least one of carbon nanotubes (CNT), carbon nanofibers (CNF), metal fibers, vapor-grown carbon fibers (VGCF), and graphene.

[0047] In some exemplary embodiments, the metal fiber may comprise at least one metal or an alloy thereof selected from copper (Cu), nickel (Ni), aluminum (Al), iron (Fe), silver (Ag), gold (Au), platinum (Pt), zinc (Zn), and titanium (Ti). Thus, the coating layer having the inherent mechanical properties of the metal, as well as electrical conductivity, heat resistance, and corrosion resistance, can be formed.

[0048] In exemplary embodiments, the conductive material of the present invention may include a particulate conductive material. The particulate conductive material may include, for example, any one of carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and Denka black.

[0049] In exemplary embodiments, the content ratio of the conductive material to the boron may be 0.1 to 30% by weight. If the content ratio of the conductive material to the boron is less than 0.1%, a coating layer with low conductivity is formed, which may degrade the output performance of the battery. Additionally, if the content ratio of the conductive material to the boron exceeds 30%, it is difficult to stably fix the conductive material within the coating layer, and unwanted side reactions may be induced during repeated charging, discharging, or storage of the battery.

[0050] The average thickness of the coating layer may be, for example, about 10 nm to about 100 nm, but is not limited thereto. However, if the thickness of the coating layer is 10 nm or less, the function of effectively blocking the negative electrode active material from the electrolyte is weak, so an electrolyte decomposition reaction occurs, and consequently, lithium ions are consumed, which may increase the irreversible capacity of the battery. In addition, if the thickness of the coating layer is 100 nm or more, the electron conduction between particles of the negative electrode active material is hindered, and the input / output performance of lithium ions may be degraded.

[0051] The above negative electrode active material for a lithium secondary battery can be manufactured by preparing the above carbon-based particles, mixing them with a coating solution to form a mixture, and then heat-treating the mixture.

[0052] In exemplary embodiments, the coating solution can be prepared by dispersing a boron source and a conductive material in a solvent. For example, since B2O3 or H3BO3 is soluble in solvents such as water and ethanol, the coating solution can be prepared by dissolving them together with the conductive material. In this case, the dispersion can be performed using methods commonly used in the industry, and the dispersion process can be carried out using an ultrasonic dispersion device, a bead mill, a high-speed blade rotation type dispersion mill, etc. Accordingly, the conductive material, consisting of nanometer-sized particles, can be evenly dispersed within the coating solution without clumping.

[0053] In exemplary embodiments, the weight ratio of the boron source to the conductive material may be 20:1 to 2:1. More preferably, the weight ratio of the boron to the conductive material may be 20:1 to 10:3. If the weight ratio of the conductive material to the boron is less than 20:1, the conductive network formed in the coating layer by the conductive material may be insufficiently formed. Additionally, if the weight ratio of the conductive material to the boron exceeds 2:1, it is difficult for the conductive material to be completely dispersed within the coating solution, and the conductive material may not be stably fixed during the formation of the coating layer.

[0054] The above heat treatment can be performed by heat-treating the dried material in an atmospheric or inert gas atmosphere. For example, the heat treatment can be performed at 400 to 600°C for 10 minutes to 3 hours. Accordingly, the coating layer can be firmly fixed through adhesion by melting and chemical bonding with functional groups on the surface of the negative electrode active material, thereby improving the long-term life performance of the battery.

[0055] In some embodiments, a drying step may be further performed before the heat treatment step.

[0056] The above drying can be performed at a temperature ranging from room temperature to 150°C. In addition, various drying equipment such as ring dryers, conveyor belt continuous drying, multi-stage batch drying, and multi-stage rotary continuous drying can be used, and drying can be performed using various heat sources such as natural air drying, hot air drying by electric heaters, and drying by infrared heaters and microwaves. Therefore, the primary coating of the coating solution can be achieved with only a simple process, and the coating layer can be formed on the surface of the cathode active material.

[0058] < lithium secondary battery >

[0059] FIGS. 1 and FIGS. 2 are a schematic plan view and a cross-sectional view, respectively, showing a lithium secondary battery according to exemplary embodiments.

[0060] Referring to FIGS. 1 and 2, a lithium secondary battery may include an electrode assembly comprising a positive electrode (100), a negative electrode (130), and a separator (140) interposed between the positive electrode and the negative electrode, and the electrode assembly may be impregnated and contained together with an electrolyte in a case (160).

[0061] The positive electrode (100) may include a positive electrode active material layer (110) formed by applying a slurry containing the positive electrode active material to a positive electrode current collector (105).

[0062] The positive current collector (105) may be made of aluminum or an aluminum alloy, but is not limited thereto, and may be made of stainless steel, nickel, aluminum, titanium or an alloy thereof, or aluminum or stainless steel with a surface treatment of carbon, nickel, titanium, or silver.

[0063] The above positive active material may include a compound capable of reversibly intercalating and deintercalating lithium ions.

[0064] In exemplary embodiments, the positive electrode active material may comprise a lithium-transition metal oxide. For example, the lithium-transition metal oxide comprises nickel (Ni) and may further comprise at least one of cobalt (Co) or manganese (Mn).

[0065] For example, the above lithium-transition metal oxide can be represented by the following chemical formula 1.

[0066] [Chemical Formula 1]

[0067] Li 1+a Ni 1-(x+y) Co x M y O2

[0068] In the above chemical formula 1, -0.05≤α≤0.15, 0.01≤x≤0.3, 0.01≤y≤0.3, and M may be one or more selected elements selected from Mn, Mg, Sr, Ba, B, Al, Si, Ti, Zr, or W.

[0069] A slurry can be prepared by mixing and stirring the above positive active material with a binder, a conductive material and / or a dispersant, etc., in a solvent. A positive electrode (100) can be prepared by coating the slurry onto a positive electrode current collector (105), and then compressing and drying it.

[0070] The above solvent may typically be a non-aqueous solvent. For example, N-methyl-2-pyrrolidone (NMP), dimethylformamide, dimethylacetamide, N,N-dimethylaminopropylamine, ethylene oxide, tetrahydrofuran, etc. may be used, but are not limited thereto.

[0071] The above binder may be used in the field without any particular limitations. For example, it may include organic binders such as vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidenefluoride (PVDF), polyacrylonitrile, and polymethylmethacrylate, or water-based binders such as styrene-butadiene rubber (SBR), and may be used together with a thickener such as carboxymethyl cellulose (CMC).

[0072] In this case, a PVDF-based binder can be used as the positive electrode binder. Therefore, the amount of binder required to form the positive electrode active material layer can be reduced, and the amount of the positive electrode active material can be relatively increased, thereby improving the output and capacity of the secondary battery.

[0073] The above conductive material may be included to promote electron transfer between active material particles. For example, the conductive material may include carbon-based conductive materials such as graphite, carbon black, graphene, carbon nanotubes, etc., and / or metal-based conductive materials such as perovskite materials such as tin, tin oxide, titanium oxide, LaSrCoO3, LaSrMnO3, etc.

[0074] The cathode (130) may include a cathode active material layer (120) by applying a slurry containing a cathode active material to a cathode current collector (125).

[0075] The negative electrode (130) for a lithium secondary battery of the present invention can be manufactured by mixing and stirring a solvent, and if necessary, a binder, a conductive material, a dispersant, etc., with the aforementioned negative electrode active material to prepare a slurry, then applying (coating) the slurry to a negative electrode current collector (125), compressing it, and then drying it.

[0076] Non-aqueous solvents can typically be used as solvents. Examples of non-aqueous solvents include N-methyl-2-pyrrolidone (NMP), dimethylformamide, dimethylacetamide, N,N-dimethylaminopropylamine, ethylene oxide, tetrahydrofuran, etc., but are not limited thereto.

[0077] As for the binder, any binder used in the field may be used without any particular restrictions. For example, organic binders such as vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidenefluoride (PVDF), polyacrylonitrile, and polymethylmethacrylate, or water-based binders such as styrene-butadiene rubber (SBR) may be used together with a thickener such as carboxymethyl cellulose (CMC).

[0078] The content of the binder can be set to an amount necessary to form the electrode and is not subject to any particular limitations, but in order to improve resistance characteristics within the electrode, it may be 5% by weight or less of the total weight of the negative electrode active material and the binder. Meanwhile, the lower limit of the binder content is not specifically limited, but it is sufficient to maintain the function of the electrode, and for example, it may be 0.5% by weight or 1% by weight of the total weight of the negative electrode active material and the binder.

[0079] Conventional conductive carbon materials can be used as conductive materials without any particular restrictions.

[0080] The negative electrode current collector (125) is a metal that has high conductivity and allows the slurry of the negative electrode active material to adhere easily, and any metal that is non-reactive in the voltage range of the battery can be used. For example, copper or a copper alloy may be used, but is not limited thereto, and stainless steel, nickel, copper, titanium or alloys thereof, or copper or stainless steel with carbon, nickel, titanium, or silver surface treated on the surface may be used.

[0081] The above slurry can be coated onto at least one surface of the cathode current collector (125), and then compressed and dried to produce a cathode (130).

[0082] According to one embodiment of the present invention, the electrode density of the negative electrode active material layer (120) formed by coating the negative electrode active material is, for example, 1.45 g / cm³. 3 It may be above, and the upper limit is not specifically restricted. If the electrode density of the cathode satisfies the above range, the output, lifespan, and high-temperature storage characteristics can be improved during electrode manufacturing.

[0083] A separator (140) may be interposed between the anode (100) and the cathode (130). The separator (140) may include a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, an ethylene / methacrylate copolymer, etc. The separator (140) may also include a nonwoven fabric formed of high-melting-point glass fibers, polyethylene terephthalate fibers, etc.

[0084] In some embodiments, the area (e.g., the contact area with the separator (140)) and / or volume of the negative electrode (130) may be larger than that of the positive electrode (100). Accordingly, lithium ions generated from the positive electrode (100) can move smoothly to the negative electrode (130) without precipitating, for example, in the middle. Thus, the effect of capacity and output improvement due to the adoption of the silicon-based negative electrode active material described above can be more easily realized.

[0085] According to exemplary embodiments, an electrode cell is defined by an anode (100), a cathode (130), and a separator (140), and a plurality of electrode cells may be stacked to form, for example, an electrode assembly (150) in the form of a jelly roll. For example, the electrode assembly (150) may be formed by winding, laminating, folding, etc., of the separator (140).

[0086] A lithium secondary battery can be defined by housing an electrode assembly (150) together with an electrolyte within an outer case (160). According to exemplary embodiments, a non-aqueous electrolyte may be used as the electrolyte.

[0087] The non-aqueous electrolyte comprises a lithium salt as an electrolyte and an organic solvent, and the lithium salt is, for example, Li + X - It is expressed as and the anion (X) of the above lithium salt - As F - , Cl -, Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - Examples of the back can be given.

[0088] Examples of the above organic solvents may include propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethylmethyl carbonate (EMC), methylpropyl carbonate, dipropyl carbonate, dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, vinylene carbonate, sulfolane, gamma-butyrolactone, propylene sulfite, and tetrahydrofuran. These may be used individually or in combination of two or more.

[0089] As illustrated in FIG. 1, electrode tabs (positive tabs and negative tabs) may protrude from the positive current collector (105) and negative current collector (125) belonging to each electrode cell and extend to one side of the outer case (160). The electrode tabs may be fused together with the one side of the outer case (170) to form electrode leads (positive leads (107) and negative leads (127)) that extend or are exposed to the outside of the outer case (170).

[0090] The above lithium secondary battery can be manufactured in, for example, a cylindrical, prismatic, pouch, or coin type using a can.

[0091] Hereinafter, preferred embodiments are presented to aid in understanding the present invention; however, these embodiments are merely illustrative of the invention and are not intended to limit the appended claims. It is obvious to those skilled in the art that various changes and modifications to the embodiments are possible within the scope and spirit of the invention, and that such variations and modifications fall within the scope of the appended claims.

[0093] Examples and Comparative Examples

[0094] <Cathode>

[0095] 100 g of carbon-based particles composed of graphite-based materials with an average particle diameter of 11 μm were prepared. 0.5 g of B2O3 and 0.15 g of carbon nanotubes (CNT) were added to ethanol, and a coating solution was prepared through ultrasonic dispersion treatment.

[0096] After mixing the carbon-based particles and the coating solution, a mixture was prepared by mechanically mixing at 2200 rpm for 10 minutes in a high-speed stirrer, and a negative electrode active material with a uniformly formed coating layer on the surface was manufactured by drying sufficiently at a temperature of 120°C.

[0097] Next, a carbon-based particle-coating layer cathode active material was prepared by forming a coating layer on the surface of the carbon-based particles by performing heat treatment on the dried material at a temperature of 450°C for 30 minutes in an atmospheric environment.

[0098] Subsequently, the prepared negative electrode active material PVDF is mixed in a mass ratio of 95:5 and dispersed in an NMP solvent to prepare a composition; the composition is applied to one side of a Cu-foil current collector, dried, and rolled to form a negative electrode active material layer measuring 10 cm × 10 cm × 50 µm, thereby achieving an electrode density of 1.50 ± 0.05 g / cm³ 3 , loading amount 12.8 mg / cm² 2 The cathode was fabricated.

[0100] * <Polar>

[0101] Li as a cathode active material 1.0 Ni 0.6 Co 0.2 Mn 0.2 An anode composite was prepared using O2, Denka Black as a conductive material, PVDF as a binder, and N-methyl pyrrolidone as a solvent in a mass ratio composition of 46:2.5:1.5:50, and then an anode was manufactured by coating, drying, and pressing the composite onto an aluminum substrate.

[0102] Battery

[0103] The above-mentioned anode and cathode were each notched to dimensions of 4.5 cm by 5.2 cm, respectively, and 17 sheets were stacked based on the cathode. A separator (polyethylene, thickness 25 μm) was interposed between the anode and cathode plates to form a battery, and the tab portions of the anode and cathode were welded. The welded assembly of the anode, separator, and cathode was placed inside a pouch. The portion containing the tabs was included in the sealing area, and three sides were sealed, excluding the surface for electrolyte injection. Electrolyte was injected into the remaining portion, and after sealing the remaining side, the mixture was impregnated for at least 24 hours. The electrolyte was prepared by preparing a 1M LiPF6 solution using a mixed solvent of ethylene carbonate (EC) / ethylmethyl carbonate (EMC) / diethylene carbonate (DEC) (25 / 45 / 30; volume ratio), and then adding 1 wt% vinylene carbonate (VC), 0.5 wt% 1,3-propensulfone (PRS), and 0.5 wt% lithium bis(oxalateto)borate (LiBOB).

[0104] Coincell

[0105] A composition is prepared by mixing a cathode active material, styrene butadiene rubber (SBR), and carboxymethylcellulose (CMC) as a thickener in a mass ratio of 97.3:1.5:1.2 and then dispersing the mixture in deionized distilled water; the composition is applied to one side of a Cu-foil current collector, dried, rolled, and punched to produce a circular disc-shaped electrode with a size of 1.2 cm² and a density of 1.60 ± 0.05 g / cm². 3 , loading dose: 8 mg / cm² 2 The cathode of was manufactured.

[0106] A 2016 type coin cell was manufactured by using lithium metal foil as the negative electrode and counter electrode prepared above, and impregnating the electrode with an electrolyte solution in which 1M LiPF6 is dissolved in a mixed solvent of ethylene carbonate (EC) / ethyl methyl carbonate (EMC) / diethylene carbonate (DEC) (25 / 45 / 30; volume ratio) with a separator (polyethylene, thickness 25㎛) in between.

[0108] Example 2

[0109] In the secondary battery manufacturing process of Example 1, a secondary battery was manufactured in the same manner except that 1.0 g of B2O3 was included in the coating solution.

[0111] Example 3

[0112] In the secondary battery manufacturing process of Example 1, a secondary battery was manufactured in the same manner except that 1.5g of B2O3 was included in the coating solution.

[0114] Comparative Example 1

[0115] In the secondary battery manufacturing process of Example 1, a secondary battery was manufactured in the same manner except that carbon nanotubes (CNT) were not added to the coating solution.

[0117] Comparative Example 2

[0118] In the secondary battery manufacturing process of Example 2, a coating solution containing 1.0 g of triphenylphosphate instead of B2O3 was prepared to form a coating layer on the surface of carbon-based particles.

[0120] Comparative Example 3

[0121] In the secondary battery manufacturing process of Example 1, a secondary battery was manufactured in the same manner except that a coating solution was not used.

[0123] Experimental Example

[0124] Raman Spectroscopic Analysis

[0125] Raman spectroscopic analysis was performed on the cathode active materials according to the above examples and comparative examples. The laser wavelength of the Raman spectrometer was approximately 532.06 nm, the laser output was 11.87 mW, the number of scans was 1, and the laser exposure time was 20 seconds; the R value is the intensity of the D band (I) in the Raman spectrum for the particle. d ) and G band intensity (I g The ratio of )(I d / I gIt means ).

[0126] The intensity of the above G band (I g ) is 1,540cm -1 Over 1,620cm -1 The peak intensity for the wavenumber region below, and the intensity of the D band (I d ) is 1,300cm -1 Over 1,420 cm -1 The following shows the peak intensity for the wavenumber region.

[0127] <Measurement of Boron and Conductive Material Content in Active Material Particles>

[0128] ICP analysis was performed to measure the boron content in the cathode active material according to the above examples and comparative examples. The analysis method is as follows. 0.01 g of the sample was placed in a PP tube, nitric acid and hydrogen peroxide were added, and the tube was sealed to perform primary dissolution at room temperature. Subsequently, the tube was opened, heated and cooled in a heating block, and diluted with ultrapure water to prepare the analytical reagent. Insoluble components in the analytical reagent were removed using a 0.45 µm syringe filter, and the sample was analyzed using an Optima 8300 model. The measurement conditions were RF Power 1500 W, Coolant gas 10 L / min, Auxiliary gas 0.2 L / min, and Carrier gas 0.65 L / min. The content of the conductive material was determined based on the input amount.

[0130] The measured values ​​according to the above-described experimental examples are shown in Table 1 below.

[0131] division I D / I G Boron content (ppm) Conductive material content (%) Example 1 0.1 119 0.149 Example 2 0.13 440 0.149 Example 3 0.15 490 0.148 Comparative Example 1 0.09 117 0 Comparative Example 2 0.3 0 0 Comparative Example 3 0.033 0 0

[0132] Referring to Table 1, the Raman R values ​​of the examples were found to be more than 30 times higher than those of the comparative example in which no coating layer was formed, and the examples had a coating layer containing boron and a conductive material formed.

[0134] <Initial Charge / Discharge Measurement>

[0135] For the coin cells according to the examples and comparative examples, charging (CC / CV 0.1C 0.005V 0.01C CUT-OFF) and discharging (CC 0.1C 1.5V CUT-OFF) were performed once to measure the initial charge and discharge capacities. (CC: constant current, CV: constant voltage)

[0137] <Initial Efficiency Measurement>

[0138] The initial efficiency was measured as a percentage value obtained by dividing the above-mentioned initial discharge amount by the initial charge amount.

[0140] <Rate Characteristics Evaluation>

[0141] For the coin cells according to the examples and comparative examples, charging (CC / CV 0.1C 0.005V 0.01C CUT-OFF) and discharging (CC 0.1C 1.5V CUT-OFF) were performed 10 times, and then charging (CC / CV 0.1C 0.005V 0.01C CUT-OFF) and discharging (CC 3.0C 1.5V CUT-OFF) were performed once more. The rate characteristic was evaluated by converting the value obtained by dividing the 3.0C discharge capacity by the 0.1C discharge capacity into a percentage (%).

[0143] <Measurement of Capacity Retention (Lifestyle Characteristics)>

[0144] For battery cells according to the examples and comparative examples, lifespan is defined as the percentage of the value obtained by dividing the discharge capacity at 200 cycles by the discharge capacity at 1 cycle, after repeating charging (CC / CV 0.5C 4.3V 0.05C CUT-OFF) and discharging (CC 1.0C 3.0V CUT-OFF) 200 times.

[0146] <Measurement of Mars Gas Emissions>

[0147] For the batteries according to the examples and comparative examples, the initial gas release amount was measured by measuring the volume of the battery before and after pre-charge using the specific gravity measurement method.

[0148] For the gas measuring cell, only Pre-charge (charging condition CC 0.25C 48 min. CUT-OFF) was performed, and the specific gravity of the cell was measured within 3 hours, and the amount of gas generated relative to the initial state was calculated.

[0149] Measurement preparation;

[0150] Prepare a sample (1Ah cell).

[0151] Prepare a water tank on a balance with a resolution of 0.001g or more so that the sample can be sufficiently submerged, and fill the water tank with water so that the cell can be sufficiently submerged.

[0152] Deion-removed DI-water is used. At this time, the balance is zeroed. To minimize changes in water specific gravity, evaporation rate, etc., the temperature of the measurement room is maintained at a constant 23 degrees.

[0153] Measurement of cell weight;

[0154] The Mars cell is weighed outside the tank before being placed in the tank. This is called the weight outside the water.

[0155] Next, the submerged weight of the Mars-type cell is measured. The cell is placed inside a balance that has been filled with water and zeroed, and its weight is recorded. This is referred to as the submerged weight of the cell. After measurement, the moisture on the surface of the cell is wiped off, and it is left at room temperature to dry completely.

[0156] Calculation of cell volume;

[0157] To determine the specific gravity of water, the temperature of the DI-water in the tank is measured.

[0158] The volume of the cell is calculated using the following formula.

[0159] Cell volume (ml) = ((Weight outside water, g) - (Weight inside water, g)) / Specific gravity of water ( 0.99754 g / cc @23℃)

[0160] Calculation of Mars gas volume;

[0161] The volume of Martian gas is calculated by subtracting the volume of the pre-Martian cell from the volume of the post-Martian cell measured by the above method.

[0163] The measured values ​​according to the above-described experimental examples are shown in Table 2 below.

[0164] division Coin cell initial charge (mAh / g) Coin cell initial discharge amount (mAh / g) Coin cell initial irreversible capacity (mAh / g) Coin cell initial efficiency Coin cell rate characteristics Battery cell lifespan characteristics Mars gas emissions (ml) Example 1 393.3 360.6 32.7 91.7% 97.4% 96.3% 1.3 Example 2 387.1 358.2 28.9 92.5% 98.5% 96.7% 1.1 Example 3 386.5 356.3 30.2 92.2% 95.1% 95.9% 1.2 Comparative Example 1 388.1 357.4 30.7 92.1% 92.3% 93.8% 1.2 Comparative Example 2 394.8 358.3 36.5 90.8% 88.4% 93.2% 2.8 Comparative Example 3 399.7 355.6 42.1 89.0% 78.2% 92.3% 3.0

[0166] Referring to Table 2, in the case of the examples containing boron oxide and carbon nanotubes in the coating layer, overall superior charge / discharge efficiency and capacity retention rate were obtained compared to the comparative examples.

[0167] In the case of Comparative Example 1, in which the coating layer does not contain a conductive material, the initial efficiency and rate characteristics were significantly reduced due to the inorganic coating layer with low conductivity. In addition, the mechanical strength of the coating layer was low, it could be easily detached, and the lifespan characteristics were degraded.

[0168] In the case of Comparative Example 2, which has a coating layer containing triphenyl phosphate instead of boron oxide, the electrolyte wettability decreased, and the initial efficiency and lifespan characteristics deteriorated compared to the examples.

[0169] In the case of Comparative Example 3, which used carbon-based particles without a coating layer as the negative electrode active material, the charge / discharge efficiency and lifespan characteristics were reduced compared to the examples. In addition, the negative electrode active material with a coating layer secured oxidation resistance, thereby reducing the amount of oxidized gas released during the calcination process. Explanation of the symbols

[0171] 100: Anode 105: Positive current collector 110: Positive active material layer 120: Cathode active material layer 125: Cathode current collector 130: Cathode 140: Separator 150: Electrode assembly 160: Case

Claims

Claim 1 A negative electrode active material for a lithium secondary battery, comprising carbon-based particles; and a coating layer bonded to at least a portion of the surface of the carbon-based particles, wherein the coating layer comprises boron (B) and a linear conductive material. Claim 2 A negative electrode active material for a lithium secondary battery according to claim 1, wherein the coating layer comprises a boron compound. Claim 3 A negative electrode active material for a lithium secondary battery according to claim 1, wherein the linear conductive material comprises at least one of carbon nanotubes (CNT), carbon nanofibers (CNF), metal fibers, vapor-grown carbon fibers (VGCF), and graphene. Claim 4 A negative electrode active material for a lithium secondary battery according to claim 3, wherein the metal fiber comprises at least one metal selected from copper (Cu), nickel (Ni), aluminum (Al), iron (Fe), silver (Ag), gold (Au), platinum (Pt), zinc (Zn), and titanium (Ti), or an alloy thereof. Claim 5 A negative electrode active material for a lithium secondary battery according to claim 1, wherein the carbon-based particles comprise at least one of artificial graphite, natural graphite, graphitized carbon fiber, graphitized mesocarbon microbeads, petroleum coke, resin calcined body, carbon fiber, activated carbon, and pyrolytic carbon. Claim 6 A negative electrode active material for a lithium secondary battery according to claim 1, wherein the content ratio of the conductive material to the boron is 0.1% to 30% by weight. Claim 7 A negative electrode active material for a lithium secondary battery according to claim 1, wherein the thickness of the coating layer is 10 nm to 100 nm. Claim 8 A method for manufacturing a negative electrode active material for a lithium secondary battery, comprising the steps of: preparing carbon-based particles; preparing a coating solution by dispersing a boron (B) source and a linear conductive material in a solvent; mixing the carbon-based particles and the coating solution to produce a mixture; and heat-treating the mixture. Claim 9 A method for manufacturing a negative electrode active material for a lithium secondary battery according to claim 8, wherein the mixing weight ratio of the boron source and the conductive material is 20:1 to 2:

1. Claim 10 A method for manufacturing a negative electrode active material for a lithium secondary battery according to claim 8, wherein the solvent comprises at least one of water or ethanol. Claim 11 A method for manufacturing a negative electrode active material for a lithium secondary battery according to claim 8, wherein the heat treatment is performed in an atmospheric or inert gas atmosphere and at a temperature of 400°C to 600°C. Claim 12 A lithium secondary battery comprising: a negative electrode comprising a negative electrode active material for a lithium secondary battery according to any one of claims 1 to 7; a positive electrode; and a separator interposed between the negative electrode and the positive electrode.